Religiosity in the Generation Z Era: Its Impact on the Ethical Perceptions of Prospective Accountants - Nuraisyah Zain Mide; Hasiah (CV Edujavare Publishing, 2026)
This research is motivated by the increasing number of cases of ethical violations in the accounting profession, which indicates the importance of developing ethical perceptions among prospective accountants during their higher education. This study aims to analyze the influence of religiosity on the ethical perceptions of prospective accountants of Generation Z and to examine the moderating role of knowledge of accounting professional ethics on this relationship. The study population was students of the Accounting Department of Politeknik Negeri Ujung Pandang, with purposive sampling as the sampling technique. Data were obtained through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that religiosity has a positive and significant effect on the ethical perceptions of prospective accountants of Generation Z. However, knowledge of accounting professional ethics is unable to moderate the relationship between religiosity and ethical perceptions. This study concludes that religiosity is an important factor in shaping the ethical perceptions of accounting students, while knowledge of professional ethics has not been able to strengthen the influence of religiosity on the ethical perceptions of prospective accountants.